Nonalcoholic Fatty Liver Disease and Coronary Artery Disease: Big Brothers in Patients with Acute Coronary Syndrome - Mauricio Montemezzo; Ahmed AlTurki; Fabio Stahlschmidt; Marcia Olandoski; Jean Rodrigo Tafarel; Dalton Bertolin Precoma (The Scientific World Journal)
Background. The prevalence of nonalcoholic fatty liver disease (NAFLD) has been increasing. This study aimed to evaluate the prevalence of NAFLD, as diagnosed by ultrasound, in patients with acute coronary syndrome (ACS) and to assess whether NAFLD is associated with the severity of coronary obstruction as diagnosed by coronary angiography. Methods. We performed a prospective single-center study in patients hospitalized due to acute coronary syndrome who underwent diagnostic coronary angiography. Consecutive patients who presented to the emergency room were diagnosed with acute coronary syndrome and were included. All patients underwent ultrasonography of the upper abdomen to determine the presence or absence of NAFLD; NAFLD severity was graded from 0 to 3 based on a previously validated scale. All patients underwent diagnostic coronary angiography in the same hospital, with the same team of interventional cardiologists, who were blinded to the patients’ clinical and ultrasonographic data. CAD was then angiographically graded from none to severe based on well-established angiographic criteria. Results. This study included 139 patients, of whom 83 (59.7%) were male, with a mean age of 59.7 years. Of the included patients, 107 (77%) patients had CAD, 63 (45%) with serious injury. Regarding the presence of NAFLD, 76 (55.2%) had NAFLD including 18 (23.6%) with grade III disease. In severe CAD, 47 (60.5%) are associated with NAFLD, and 15 (83.3%) of the patients had severe CAD and NAFLD grade III. Conclusions. NAFLD is common in patients with ACS. The intensity of NAFLD detected by ultrasonography is strongly associated with the severity of coronary artery obstruction on angiography.